AUDIT ENERGI LISTRIK PADA PUSAT PERBELANJAAN DEPARTMENT STORE MATAHARI A. YANI MEGA MALL PONTIANAK - Muslimin . (Faculty of Engineering, Universitas Tanjungpura, 2016)
Determining IKE (intensity of energy consumption) as well as the cost of payment according to usage based on historical data Matahari Department Store Mega Mall Pontianak using one of the methods currently used for the efficient use of electric energy is the electrical energy audit. Electric energy audit is to increase the efficiency of energy used or the energy savings. The goal of the energy audit is to look for ways to reduce energy consumption unity output and reduce operating costs. IKE electricity in electricity consumption in the Sun A. Yani Mega Mall widely conditioned Pontianak year a detailed audit results (measurement results) obtained a value of 331.48 kWh / m2, is still far from the value of the existing standard is for the shopping center is 330 kWh / m2 year. From the data analysis of electrical energy consumption in shopping centers A. Yani Mega Mall Pontianak during the day obtained electricity consumption for air conditioning at 5844.04 kWh, for the lamp at 927.45 kWh, for other devices for 165 kWh. Enterprises consumption savings directed towards businesses replacement refrigerant, it is taken because they amount of operating the air conditioner in the room more than one AC that operates so as to do the replacement refrigerant in rotation, but the first observation and checking carefully to the various aspects of the machine aspect of the machine AC.Replacement of refrigerant by using Musicool, which Musicool refrigerant is a natural refrigerant materials that are environmentally friendly type of hydrocarbon that is a substitute refrigerant sintetic halocarbons group CFC R-12, HCFCR HFC-22 and R-134a which still has the potential to destroy nature. From the results of the implementation of energy-saving opportunities (PHE), the analysis of the savings obtained from sintetic types HCFC refrigerant replacement for R-22 using the brand Musicool in every air conditioner installed in the shopping center Mega Mall Sun A. Yani Pontianak, obtained results that the a decrease in the total energy consumption of electricity per day, which before the replacement of freon Musicool obtained total electrical energy consumption amounting to 5844.04 kWh, but after replacement of total electricity to be obtained 5089.76 kWh, and the results of calculations and analysis for the replacement of general lighting lamps with energy saving lamps LEDs installed in A. Yani Mega Mall Pontianak obtained a reduction in total energy consumption of electricity per day, Diman before replacement LED energy saving lamp gained 927.25 kWh total energy consumption, but after a replacement is obtained 729.84 kWh. To target IKE per unit area are conditioned to shopping centers amounted to 330 kWh / m2 a year.It turns before performs IKE implementation IKE value PHE A. Yani Mega Mall Pontianak amounted to 331.48 kWh / m2 and after and PHE IKE value of 296.68 kWh / m2. in the shopping center Mega Mall Sun A. Yani Pontianak seen already in accordance with the standards or target of electricity IKE. The amount of costs incurred after the implementation of the PHE for air conditioning Rp. 18.75 million, - and the total cost for LED replacement lamp Rp. 539 700 000, - the durability of 5 years. The cost savings for a year after implementing PHE is Rp. 463,226,388.5, - Keywords: IKE (Intensity of Energy Consumption), Energy Audit, PHE (Energy Saving Opportunity)